Rancangan Sistem Siklus Akuntansi Pada Bank Sampah - Anis Indah Kurnia; Dadang Romansyah (SEKOLAH TINGGI EKONOMI ISLAM SEBI, 2015)
This study aims to formulate a system of accounting cycle on trash bank. This studyused descriptive methods and qualitative data. This study’s subjects consisted of respondents and the data library that collected by interviews, documentation and literature. Analysis was done by analyze the data to understand the process of accounting cycle, preparing the system, the last summed up the results of analysis. The study found a system of financial records and financial statements based on SAK ETAP and some contract in PSAK Sharia. Accounting system has a preparation, recording and classification stage. The preparation stage such as chart of account, price list and customers list. The recording stage such as ledgers: trash inventory, savings cooperatives, list of net income cooperatives, list of savings, list of lending, list of electrical and pulse supplies and special journals: purchase of trash, sales of trash, saving of trash, cash receipts and cash payments. The classification stage such as general ledger, adjusting entries, trial balance. Then the system of financial statements consist of balance sheet, income statement, equity statement, cash flow statement and notes to the financial statements. Finally, for the preparation next period there are after closing journal and trial balance after closing.